Diagnosis of technical gas turbine engine by using the nearest "neighbor" - Якушенко, О.С. (Proceedings of National Aviation University (archive), 2008)
In the paper the problem of nearest "neighbor" method using for identification of aircraft gas turbine engines technical condition is considered. The results of the method using are given.